2017
DOI: 10.1002/jcp.25805
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of blue light emitting diode on migration and invasion of cancer cells

Abstract: The aim of this study was to determine the effects and molecular mechanism of blue light emitting diode (LED) in tumor cells. A migration and invasion assay for the metastatic behavior of mouse colon cancer CT-26 and human fibrosarcoma HT-1080 cells was performed. Cancer cell migration-related proteins were identified by obtaining a 2-dimensional gel electrophoresis (2-DE) in total cellular protein profile of blue LED-irradiated cancer cells, followed by matrix-assisted laser desorption/ionization-time of flig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 33 publications
7
32
1
Order By: Relevance
“…5), suggesting the increase in metabolic activity does not translate into increased proliferation, but rather into restoration of the epidermal barrier. Indeed, low-dose blue light did not modulate migration of keratinocytes, while a high dose of 30 J/cm 2 had an inhibitory effect, in line with reports on cultured dermal fibroblasts [24,68].…”
Section: Discussionsupporting
confidence: 88%
“…5), suggesting the increase in metabolic activity does not translate into increased proliferation, but rather into restoration of the epidermal barrier. Indeed, low-dose blue light did not modulate migration of keratinocytes, while a high dose of 30 J/cm 2 had an inhibitory effect, in line with reports on cultured dermal fibroblasts [24,68].…”
Section: Discussionsupporting
confidence: 88%
“…Notable among the various species of LED is that blue LED with 430-490 nm wavelengths showed excelent antitumor activity in vitro and in vivo experiments. Blue light could effectively inhibit the tumor progress of skin tumors, melanoma, leukemia, colon cancer mainly depending on the accumulation of intracellular reactive oxygen species (ROS) [8][9][10][11]. Consistent with these reports, our previous study demonstrated that blue LED could enhance the anti-tumor effects of arsenic trioxide on human osteosarcoma and cause cell death in colorectal cancer through increasing ROS accumulation and DNA damaged mediated p53 activation [12,13].…”
Section: Introductionsupporting
confidence: 68%
“…Even though the thermal and mechanical effects caused by 460 nm LED and ultrasound are still under research, LED and ultrasound devices could effectively reduce cancer cell viability with signaling effects to the cells and cavitation effects [5,25]. For LED, light irradiation inhibits the signaling between cancer cells, thus inducing cell death without thermal increments [9]. For ultrasound, cavitation effects are produced in the tissues to collapse gaseous cavities in a medium.…”
Section: In Vitro Hela Cell Experiments With Designed Instrumentationmentioning
confidence: 99%
“…Moreover, blue LED light has been reported to suppress melanoma and retinal pigment epithelium cells because it generates intracellular oxygen species that can induce apoptosis without any thermal effects [7,8]. However, the thermal mechanism of the signaling pathways for suppressing cancer cells in blue LED-based phototherapy is still under exploration [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation